Reluctant transformers or reconsidering opposition to climate change mitigation? German think tanks between environmentalism and neoliberalism - Dieter Plehwe (Globalizations, 2022)
Germany is known as a leader in energy transition, but the country keeps falling short of meeting stated objectives. While attention has been high on climate change related policy leadership, the competing domestic alliances in the field of energy transition have received scant attention. In Germany, the strong momentum of the conversion to renewable energy has been stalled in the second half of the 2010s. Enabled by an increasing weight of neoliberal economic concerns, traditional energy coalitions have managed to reshape the path of energy transition. In this article three competing discourse coalitions are introduced to examine their constituencies and projects in the field of energy and politics. It focuses on radical ecological forces around the Öko-Institut, environmental modernization capacities linked to Green Budget Germany and fossil interest groups intersecting with neoliberal academic and partisan think tanks. As such, the article opens a view on multiple contestations over Germany's Energiewende.
Keywords: 300; energy transition; Germany; climate change; neoliberalism; think tank